A review of combined economic emission dispatch for optimal power dispatch with renewable energy - N. F. Aswan; M. N. Abdullah; A. H. Abu Bakar (Institute of Advanced Engineering and Science, 2019)
This paper provides comprehensive review of recent formulation and solution of combined economic emission dispatch problem considering renewable energy. Generally, power dispatch plays an important role in power generation system that mainly depends on the fossil fuels. Rapid depletion of these sources cause a limitation and increase the fuel price. At the same time, the poisonous gases emit by the thermal generator causes a long term environmental pollution. An extensive researches have been conducted for last few decades by considering Renewable Energy (RE) in power generation system as an alternative source. Therefore, Combined Economic Emission Dispatch (CEED) of thermal and renewable energy resources currently formulated in power dispatch problem. The optimization methods that commonly used to solve the CEED problem are categorized as traditional method, non-conventional method and hybrid method. It can be concluded that non-conventional and hybrid method have great and superior solution for solving multiobjective economic emission dispatch problem. The recent research related to CEED with RE are summarized in terms of methods, test cases, conditions, types of RE and constraints. Thus, it can be useful references for the research in this area.